STRATEGI PENINGKATAN DAYA SAING USAHA MIKRO, KECIL, DAN MENENGAH DI DESA TEGALWARU, KABUPATEN BOGOR - Padyanawati, Ayu Diah; Hardjomidjojo, Hartrisari (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p15, 2019)
Micro, Small, and Medium Enterprises (MSMEs) plays an improtant role in the national economy. The fact show that although the number of MSMEs is dominant, but in generaly they face various obstacles in the development their bussiness. Some of the obstacle are: capital, marketing, raw materials, technology, management, bureaucracy, infrastructure, and partnership. The role of stakeholder, especially goverent and related agency are needed to solve this problem. Tegalwaru village is a tourist village that offer to visit MSMEs in the area. The competitiviness of MSMEs in Tegalwaru village needs to be improved in order to compete in national and international level. The result using perfomance index stated that MSMEs in Tegalwaru village still belong to primary and developed MSMEs category (index below 50 and among 51-75). Based on the performance index value, the average index for non food MSMEs is higher than those of food MSMEs. Some of non food MSMEs even reach the limit to independent category (index more than 75). Based on the performance indekx prioritized strategy for increasing competitiveness for each MSMEs can be developed. Keywords: Micro, Small, and Medium Enterprises, Performance Index, Competitiveness, Tegalwaru Village.